Memorial Volume For Stanley Mandelstam - Berkovits, Nathan [UNESP]; Brink, Lars; Chau, Ling-Lie; Phua, Kok Khoo; Thorn, Charles B. (My University, 2017)
Stanley Mandelstam (1928-2016) was one of the most influential and respected particle theorists. Coming as a young chemical engineer from South Africa to study theoretical physics in England, he quickly became a leading physicist in his field. With his deep understanding of quantum field theory, he pioneered the development of the analytic S-matrix theory as well as the path-dependent formulations for quantum gauge theories and for quantum general relativity. They are being actively used for the electroweak theory and having their imprints in lattice gauge theory and loop quantum gravity. Also he elucidated the mechanisms for quark confinement in quantum chromodynamics, constructed non-perturbative bosonization methods in 1+1 dimensions, and proved the perturbative finiteness and ß=0 of N=4 supersymmetric Yang-Mills theory. His work also led to the discovery of dual resonance models, which in turn became superstring theory. He was a leader in these developments, devoting much of his later years to the proof that the theory is perturbatively finite so it can be considered as a contender for the theory of quantum gravity. He was also a very modest and friendly man, impressing everyone with his sharp intellect as well as his humanity. This volume contains essays written by many of his friends and students, including both detailed reports on his scientific achievements as well as personal reminiscences. Also collected in the volume are some selected reprints of Mandelstam's early seminal papers and abstracts of selected papers representing the full spectrum of his contributions.